Peningkatan Kualitas Bunga Telang Melalui Perbaikan Proses Pengeringan Menggunakan Metode Taguchi - Sukma Dwi Yuliana Puspitasari Sanggup; Said Salim Dahda (Universitas Teuku Umar, 2022)
The use of Butterfly pea is widely used as a colorant in various local foods in Indonesia and Southeast Asian countries. This use is limited to foods that do not have a long shelf life. Processing and storage by drying in an effort to improve storage quality requires a special eksperimenal design to improve product quality. One of the eksperimenal designs that can be used is the Taguchi method. This research was conducted in Yosowilangun Village, Gresik Regency, there are problems that can be formulated in this study, namely